(untitled) (Jurnal Bina Praja, 2017)
Regional autonomy demands a creative and innovative local government. This paper sees the creativity of local government in preparing the roadmap. Basically, the readiness of local government in preparing SIDa roadmap is the overall condition of local government to understand the potential of the area in determining thematic roadmap. Some things that should be prepared by the local government is to prepare the regulation and mapping of SIDa personnel. Through this study, it comprehensively describes the stages that must be taken into account by the stakeholders in the region. The method used the explorative descriptive method. The results of the study are identified (1) Local Government readiness in preparing the SIDa roadmap by preparing the legal basis, coordinating with R & D institutions, integrating provincial and district/city programs, and preparing SIDa documents, (2) Elements prepared by the Provincial Government: Establishing TEAM Coordination Province, Identification of potency of local superior commodity, human resource identification, feasibility test, and identification of innovation of regency / city, (3) obstacles encountered in preparing SIDa roadmap are: still strong sectoral ego coordination team of province especially university and low commitment of local government Districts/municipalities in the implementation of innovation, the absence of SIDa actors in the implementation level of private sector/business world, budget allocation for innovation at various SKPD, and implementation of coordination team not yet run properly.